Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1177/0748233712462442
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of mercury induces autophagic cell death in rat hepatocytes

Abstract: In the present study, we attempted to elucidate the induction of autophagy in rat hepatocytes by a low concentration of mercury. Hepatocytes treated with different doses of mercuric chloride (HgCl2; 1, 2.5, 5 and 10 µM) and at different time intervals (0 min, 30 min, 1 h, 2 h and 4 h) show autophagic cell death only at 5 µM HgCl2 within 30 min of incubation. At 1 and 2.5 µM HgCl2, no cell death is recorded, while apoptosis is found at 10 µM HgCl2, as evidenced by the activation of caspase 3. Autophagic cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…The doses are well within the range of Hg and TCDD levels in exposed humans, 4042 animals 43 and in vitro studies. 44,45 Analysis of the differentially expressed genes (RNA-Seq) in the various exposures showed that 50% of the genes (486 out of 972) in the low-dose exposure (Fig. 1A) and 10% of the genes (190 out of 1888) in the high-dose exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The doses are well within the range of Hg and TCDD levels in exposed humans, 4042 animals 43 and in vitro studies. 44,45 Analysis of the differentially expressed genes (RNA-Seq) in the various exposures showed that 50% of the genes (486 out of 972) in the low-dose exposure (Fig. 1A) and 10% of the genes (190 out of 1888) in the high-dose exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite extensive efforts to use hepatic progenitor cells as an ideal source for liver repopulation (Fausto and Campell 2003), the response of oval cells to environmental signals remain largely unknown. Mercury, a ubiquitous hepatotoxicant promotes Toxicological & Environmental Chemistry 1729 exicitotoxicity (Ung et al 2010;Farooqui and Farooqui 2011) when introduced into a system, resulting in the induction of programed cell death (Shenker, Guo, and Shapiro 2000;Ben-Ozer et al 2000;Chatterjee et al 2012Chatterjee et al , 2013b. Oval cells exposed to low concentration of Hg were able to accommodate changes at the cellular level producing minimum cell death throughout the experiment.…”
Section: Discussionmentioning
confidence: 97%
“…It is difficult to detect elongated monomeric form of these proteins to complete autophagic vacuole formation Suzuki et al 2001;Hanada et al 2007). Chatterjee et al (2012Chatterjee et al ( , 2013a recently demonstrated that ATG5-ATG12 complex facilitates LC3B mediated autophagy in Hgtreated differentiated hepatocytes within 30 min of incubation and continued until 4 hr. However, the present study demonstrated significant involvement of ATG12, LC3B, and BCL2 proteins in Hg-induced oval cell death.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations